Rancang Bangun Aplikasi Web Pemilihan Rumah Menggunakan Dengan Metode Weighted Product - Wahyu Agung Nugroho (JATISI (Jurnal Teknik Informatika dan Sistem Informasi), 2023)
When looking for a house in Surabaya, we encountered difficulties in choosing a suitable house. Many people experience difficulties because existing homes do not meet the criteria they want. This results in many people choosing houses that do not match their criteria because they have to carry out surveys one by one in each housing complex. To overcome this problem, the solution is to create a website-based application for selecting houses using the weighted product method. This application will make it easier for prospective buyers to choose a house according to their wishes. The features and criteria in this application have been researched to meet the needs of prospective users in choosing a house. Prospective buyers can use this application to choose a house and determine the criteria they really need. After selecting the criteria, potential buyers will immediately know the house that best suits their needs. The hope is that this application can help prospective buyers choose the best house.